ANALISIS FINANSIAL USAHA TERNAK SAPI BALI (Bos sondaicus) DI P4S CAHAYA PURNAMA KABUPATEN KUTAI TIMUR - Al Hibnu Abdillah; Juraemi Juraemi; Taufan Purwokusumaning Daru (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2019)
Since it was established in 2010 until 2016, Bali cattle farming and its byproduct of the Agricultural and Rural Training Center (P4S = Pusat Pelatihan Pertanian dan Pedesaan Swadaya) had never been evaluated for its financial analysis. This research aimed to evaluate the financial analysis of Bali cattle farming and its byproduct in the P4S of Cahaya Purnama. This research was conducted from September to December 2016 in the P4S of Cahaya Purnama, Tepian Baru Village, Bengalon Sub-district, East Kutai District. The sample was taken by using purposive sampling method with the criterion that the cattle were 8 to 24 months old. The instruments used to analyze the data were Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit/Cost Ratio, Payback Period and Return of Investment (ROI). Bali cattle farming business consisted of the development of Bali beef cattle as the main business and manure processing as the byproduct. Manure processing business was the attempt of the manager to utilize the waste of cattle and it was expected that it was able to add income for the farmers. The model of Bali cattle development was the integration between oil palm plantation and Bali cattle farming. The research findings showed that the NPV was 9%, indicating that the business was minus with the amount of Rp. 19,393,858, so that the value of IRR was not known. The value of Net B/C Ratio was 0.97; the value of payback period was 0.83 or 9 years; and the value of ROI was minus with the percentage of 19%. Therefore, the Bali cattle farming business was not feasible to continue and there should be some improvements needed to make it better.